Valuation of debt indexed to real values I. The case of the Argentinean growth coupon: a simple model - Sergio Pernice; Federico Lopez Fagundez (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2005)
This paper is the first of a series of works whose aim is trying to provide a framework for the understanding and valuation of debt indexed to real (generally non-tradable) variables. In particular, in the present paper we develop a methodology to analytically value the new GDP-linked Argentinean warrant.
Keywords: 330